民间歌谣《月光光》初探 ：口语特点与程式 = A study of the Chinese folk songs entitled "Yue Guang Guang" : oral features and formulas - 张嘉嘉 Teo, Jia Jia (2014)
民间歌谣《月光光》靠口耳相传，流传于各个方言区，类型以童谣居多。《月光光》再现了古早人民的生活、景物和风俗习惯等。不过，随着农业社会往工商社会转型加上统一使用汉语的语言政策，承载方言与传统文化的《月光光》已和现今社会渐行渐远，因此会唱《月光光》的人越来越少了。由于《月光光》随着岁月流逝而退色，因此《月光光》的程式研究是迫在眉梢的任务。米尔曼·帕里（Milman Parry）和艾伯特·贝茨·洛德（Albert Bates Lord）师生以《荷马史诗》为研究对象，发现《史诗》的创编与表演都涉及程式的运用，本文参照帕里—洛德学说（Parry-Lord Theory）中的程式理论，对《月光光》进行剖析，探讨歌谣记忆与如何创作的问题。多数《月光光》文本的开头是“月光光，秀才郎，骑白马，过XX”,“XX”的位置又以“南塘”最多，其它还有“莲塘”、“三唐”、“田洋”等，这些相同的开头，就是歌谣中最稳定的程式。此外，本论文将运用互文理论探讨文本和文本间的互文现象。由于《月光光》的文本繁多，碍于篇幅的限制，本文只选取胡万川先生主编的台湾方言歌谣集册中的《月光光》及其异文作为本论文的分析对象。至于歌谣中以“月亮”为起兴的现象与方言等语言学范畴的问题，涉及的文化内涵甚为深广，此处无法一一涉及。本篇论文将参考陈正治的《儿歌理论与赏析》中歌谣的分类对童谣《月光光》进行归类，而抒情功能的《月光光》归为叙事歌，祈求月亮原谅的《拜月娘》则为仪式歌。本论文的第四章分析了《月光光》的口语特点，即语言、押韵和词汇，从中探讨民间歌谣的地方性、通俗性与易变性。根据网络论文和期刊文章有关《月光光》的研究来看，作者都选择了特定方言区的《月光光》进行文学与文化上的分析，探讨《月光光》的起源、发展与功能。希望通过民间歌谣《月光光》的研究记录《月光光》，引起大家对方言童谣的注意，也探讨民间歌谣对民族与传统文化的意义。笔者也有相同的期许，除了依循前人的研究方式，也希望透过《月光光》的程式研究了解歌谣的流传、记忆与创作，记录辉煌一时的《月光光》。Chinese folk song named Yue Guang Guang is an Oral Folklore. It can be found in dialects of various place and most of the texts are children’s songs. The contents of “Yue Guang Guang” represent the living style, scenes, customs and traditions of one area. However, agricultural economy style of many places had been changed into commercial nowadays. Thus, causing traditional society disconnected from modern societies. Also, the use of unified Chinese causing most of the new generation could not understand their mother tounge, i.e. Chinese dialects. Therefore, “Yue Guang Guang” is disappearing along the time. Because of disappearance of these traditional folk songs，my work which is focused on studying the “Formula” of the songs is very urgent. Since I could find the regularity of “Yue Guang Guang”, I could use “Parry-Lord Theory” which is about formula. Besides that, some texts with same topic but different contents can be analyzed by using “Intertextuality”. This project will only cover “Yue Guang Guang” from Taiwan which are arranged by Wan-chuan Hu （胡万川） because of word number restricted. Also, inspiration of moon and linguistics would not be included in this project. Children’s songs are classified by its content and function according to the children’s songs classification by Zhengzhi Chen （陈正治）. Also, the narrative songs and ceremonial songs will also classified through its content and function. In Chapter 4, I will make appreciative comments on “Yue Guang Guang” via the points of language using and literature view. Recently, researchers mark out one area of “Yue Guang Guang” and focus on studying its origin and function. Most of them hope that their studies and researches can catch audience’s attention and instilling the importance of dialect songs. This is because “Yue Guang Guang” is a collective memory and a sense of cultural, personal and group identity. After knowing the importance of “Yue Guang Guang”, I wish I could do my best to preserve it via analyzing it with multi-angles and theories.